2019
DOI: 10.1002/cb.1789
|View full text |Cite
|
Sign up to set email alerts
|

How to save the wounded self: Power distance belief's moderation of self‐identity threat and status‐related consumption

Abstract: There is ample evidence in the relevant literature to show that self‐identity threat affects consumers' behavior, psychological needs, purchasing behavior, and product choice. The present research takes self‐identity threat to another level with a focus on the moderating role of power distance belief (PDB) in the relation to self‐identity threat and status consumption. The research involves two studies. Study 1 shows that threatened participants with a high PDB prefer status goods to nonstatus goods. By contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…Second, the current research provided no test of mechanisms underlying the moderating effects of social mobility belief. Future research needs to test hypotheses implied in the current research, such as whether low subjective SES consumers who perceive low social mobility use conspicuous consumption as a symbolic compensatory strategy (Cui et al, 2020). In addition, alternative mechanisms, such as time orientation (Bak & Yi, 2020) and sense of control (Lammers & Imhoff, 2021), should also be explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the current research provided no test of mechanisms underlying the moderating effects of social mobility belief. Future research needs to test hypotheses implied in the current research, such as whether low subjective SES consumers who perceive low social mobility use conspicuous consumption as a symbolic compensatory strategy (Cui et al, 2020). In addition, alternative mechanisms, such as time orientation (Bak & Yi, 2020) and sense of control (Lammers & Imhoff, 2021), should also be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, materialistic consumers spend impulsively when they perceive low economic mobility, whereas they can resist impulsive spending when they perceive high economic mobility. Another work presents evidence that in the condition of self‐identity threat, people with high power distance belief prefer status to nonstatus goods (Cui et al, 2020). Existing work also hints at mechanisms driving the moderating effects of perceived social mobility, such as long‐term goal commitment (Yoon & Kim, 2016), symbolic compensatory need (Cui et al, 2020), or sense of control (Yoon & Kim, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, research reveals that consumers respond differently to luxury brands depending on whether they have high power distance beliefs (i.e., accepting power disparities in a culture) or low power distance beliefs (not accepting of power disparities). In particular, consumers are more likely to purchase status products (e.g., luxury products) when their self‐identity is threatened if they have higher (versus lower) power distance beliefs (Cui, Fam, Zhao, Xu, & Han, 2020). Future research might examine the possible confounding effects of these other cultural factors in the context of luxury brand rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, Grégoire et al (2010) found that customer power can influence revenge-seeking behaviour. Cui et al (2020) found that power distance beliefs moderate the relationship between self-identity threat and status consumption.…”
Section: By Power Reinstatementmentioning
confidence: 94%